1969
DOI: 10.1111/j.1469-8986.1969.tb02835.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of Combinations of Painful and Cognitive Stimuli

Abstract: Sympathetic activity (SA) was reduced when a cognitive task was imposed during an ongoing response to cold pressor. However, this reduction effect was not obtained when CP was imposed 40‐sec after the onset of a cognitive task. Rather the response level appeared to be about that which would have been obtained from cold pressor alone. These results suggest that the reduction found in the former situation is not the result of distraction due to cognitive activity per se, as we had previously proposed, but it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1969
1969
1978
1978

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…With the latter, the amount of masking changes as a function of the time interval between the presentation of the heteromodal stimuli. The suppression of pain by other stimuli seems to be well documented for two different sources of pain (Duneker, 1937), for sound, light, vibration, and heat (Benjamin, 1956), and recently more extensively for sound (e.g., Gardner, Licklider, & Weisz, 1960;Mefferd & Wieland, 1965;Sadler et al, 1969). The evident generality of the failure for contiguous responses to heteromodal stimuli to summate seems to warrant intensive investigation of the phenomenon.…”
Section: Discussion and Gonclusionsmentioning
confidence: 97%
See 1 more Smart Citation
“…With the latter, the amount of masking changes as a function of the time interval between the presentation of the heteromodal stimuli. The suppression of pain by other stimuli seems to be well documented for two different sources of pain (Duneker, 1937), for sound, light, vibration, and heat (Benjamin, 1956), and recently more extensively for sound (e.g., Gardner, Licklider, & Weisz, 1960;Mefferd & Wieland, 1965;Sadler et al, 1969). The evident generality of the failure for contiguous responses to heteromodal stimuli to summate seems to warrant intensive investigation of the phenomenon.…”
Section: Discussion and Gonclusionsmentioning
confidence: 97%
“…Previously (Sadler et al, 1969) we observed that the autonomic responses during silent reading were so much smaller than were those to cold pressor, that a failure to summate was evident only when reading was imposed during cold pressor. The purpose of the first experiment was to determine whether the response to a mild sensory stimulus imposed while >S was reading silently would summate with the ongoing reading response.…”
mentioning
confidence: 84%